Secondary metabolites from Dipterocarpus obtusifolius Teijsm. Ex Miq - Toan Phan, Nguyen Huu; Dieu Thuan, Nguyen Thi; Mai Huong, Pham Thi; Hong Hanh, Tran Thi; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Thanh, Nguyen Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
Six known compounds daphneresinol (1), (+)-neo-olivil (2), methyl gallate (3), bergenin (4), asiatic acid (5) and blumenol A (6) were obtained from the organic extract of the leaves of Dipterocarpus obtusifolius Teijsm. Ex Miq. by various chromatographic techniques. Structural elucidation of the metabolites was carried out by analysis of their spectroscopic data and by comparison with those reported in the literature. Compounds 1-4 and 6 were isolated from this plant for the first time.